Peranan Perjanjian Ekstradisi Dalam Tindak Kejahatan Korupsi di Indonesia - Ida Bagus Adi Pati Karna; Anak Agung Sagung Laksmi Dewi; I Gusti Ayu Gita Pritayanti Dinar (Jurnal Analogi Hukum, 2024)
The increase in crimes that occur in Indonesia, especially crimes that involve interstates. Therefore, extradition is a way of cooperation in combating crimes between countries, which is very important because criminals always try to flee to other countries to avoid prosecution, while on the other hand, law enforcement officials, especially the police, can only operate within the jurisdiction of their own country. Given the challenges faced in the investigation, it becomes clear how important it is to cooperate with other countries in combating this crime so that extradition agreements arise as a consequence of the existence of a legal interest in a country. The formulation of the problem is: 1. How is the legality of extradition in preventing and eradicating international crimes?  2. How is the effectiveness of extradition enforcement in a country? The research method used is normative legal research. The results of the discussion regarding the criminal law regulation of extradition crimes are contained in Law No. 1 of 1979 concerning Extradition and its effective application after an advance review of the extradition process.